2019
DOI: 10.1371/journal.pone.0223778
|View full text |Cite
|
Sign up to set email alerts
|

Life-course trajectories of body mass index and subsequent cardiovascular risk among Chinese population

Abstract: BackgroundExamining body mass index (BMI) change over life course is crucial for cardiovascular health promotion and prevention. So far, there is very few evidence on the long-term change of BMI from childhood to late life. This study aimed to examine the life-course trajectory patterns of BMI and then to link the trajectory patterns to cardiovascular risk factors in adulthood.MethodsBased on longitudinal data from the China Health and Nutrition Survey, 5276 participants (aged 6–60) at baseline (in 1989) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 37 publications
(43 reference statements)
3
50
0
Order By: Relevance
“…Five articles showed significant associations between high BMI trajectory from childhood to adulthood and increased homeostatic model assessment of insulin resistance (HOMA‐IR) levels 56 and T2D in adulthood 44,45,72,76 . The article based on the Epidemiological Health Investigation of Teenagers in Porto ( N = 719) showed that HOMA‐IR levels were higher among those assigned to the higher BMI trajectory groups in males (mean 2.41; 95% CI, 2.06–2.82) and females (mean 2.07; 95% CI, 1.84–2.32) compared with average BMI trajectory (males: mean 1.49; 95% CI, 1.36–1.63; females: mean 1.67; 95% CI, 1.55–1.79) 56 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five articles showed significant associations between high BMI trajectory from childhood to adulthood and increased homeostatic model assessment of insulin resistance (HOMA‐IR) levels 56 and T2D in adulthood 44,45,72,76 . The article based on the Epidemiological Health Investigation of Teenagers in Porto ( N = 719) showed that HOMA‐IR levels were higher among those assigned to the higher BMI trajectory groups in males (mean 2.41; 95% CI, 2.06–2.82) and females (mean 2.07; 95% CI, 1.84–2.32) compared with average BMI trajectory (males: mean 1.49; 95% CI, 1.36–1.63; females: mean 1.67; 95% CI, 1.55–1.79) 56 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table S1, 10 articles on the association between weight gain 9,12,24,25,55 or weight trajectory 44,56,60,72,76 from childhood to adulthood and adult blood pressure levels or hypertension were included in the systematic review. Three articles using BMI, 9,24,55 one using BMI Z score 25 and one using weight change 12 from childhood to adulthood as a continuous variable showed significant associations between BMI gain or weight gain and systolic blood pressure, 9,12,25 diastolic blood pressure 9,12 and hypertension 24,55 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no comparable data, we compared with other studies on BMI patterns in speci c life periods. A study conducted among the Chinese population aged 6-60 years identi ed a continuous increase of BMI in all groups of BMI (48). Some studies indicated less variability in the BMI trajectories in midlife in the total population as well as women (49)(50)(51), whereas another study reported different patterns during middle age (52).…”
Section: Discussionmentioning
confidence: 99%